The first time domain experiment with Swift: monitoring of seven nearby galaxies. Issue 7 (May 2016) - Andreoni, I; D'Avanzo, P; Campana, S; Branchesi, M; Bernardini, MG; Delia Valle, M; Mannucci, F; Melandri, A; Tagliaferri, G
Abstract: We aimed to detect a supernova (SN) shock breakout (SBO) with observations in time domain. The SBO marks the first escape of radiation from the blast wave that breaks through the photosphere of the star and launches the SN ejecta, and peaks in the ultraviolet and soft X-ray bands. The detection of a SBO allows to determine the onset of the explosion with an accuracy from a few hours to a few seconds. Using the XRT and UVOT instruments onboard the Swift satellite we carried out a weekly cadenced, six months lasting monitoring of seven nearby (distance ≤ 50Mpc) galaxies, namely NGC1084, NGC2207/IC2163, NGC 2770, NGC4303/M61, NGC 3147, NGC 3690, NGC 6754. We searched for variable/transient sources in the collected data. We found no evidence for a SN SBO event, but we discovered five objects located within the light of the sample galaxies that are variable in the X-ray and/or in the UV. Our sample galaxies are within the Universe volume that will be reached by the forthcoming advanced gravitational waves (GW) detectors (a-LIGO/a-Virgo), thus this work provides an example on how to carry out Swift surveys useful to detect the GW signal from SNe, and to detect counterparts to GW triggers.